One-Year Outcomes in Anticoagulated Atrial Fibrillation Patients Undergoing Percutaneous Coronary Intervention: Insights From the Greek Antiplatelet Atrial Fibrillation Registry. Issue 2 (February 2023) - Alexopoulos, Dimitrios; Dragona, Vassiliki-Maria; Varlamos, Charalampos; Ktenas, Dionysios; Lianos, Ioannis; Patsilinakos, Sotirios; Sionis, Dimitrios; Zarifis, Ioannis; Bampali, Theodora; Poulimenos, Leonidas; Skalidis, Emmanouil; Pissimisis, Evangelos; et al.
Abstract: GReek-AntiPlatElet Atrial Fibrillation registry is a multicenter, observational, noninterventional study of atrial fibrillation patients undergoing percutaneous coronary intervention. Primary endpoint included clinically significant bleeding rate at 12 months between different antithrombotic regimens prescribed at discharge; secondary endpoints included major adverse cardiovascular events and net adverse clinical events. A total of 647 patients were analyzed. Most (92.9%) were discharged on novel oral anticoagulants with only 7.1% receiving the vitamin K antagonist. A little over half of patients (50.4%) received triple antithrombotic therapy (TAT)—mostly (62.9%) for ≤1 month—whereas the rest (49.6%) received dual antithrombotic therapy (DAT). Clinically significant bleeding risk was similar between TAT and DAT [Hazard ratio (HR) = 1.08; 95% confidence interval (CI), 0.66–1.78], although among TAT-receiving patients, the risk was lower in those receiving TAT for ≤1 month (HR = 0.50; 95% CI, 0.25–0.99). Anticoagulant choice (novel oral anticoagulant vs. vitamin K antagonist) did not significantly affect bleeding rates ( P = 0.258). Age, heart failure, leukemia/myelodysplasia, and acute coronary syndrome were associated with increased bleeding rates. Risk of major adverse cardiovascular events and net adverse clinical events was similar between ΤAT and DAT (HR = 1.73; 95% CI, 0.95–3.18, P = 0.075 and HR = 1.39; 95% CI, 0.93–2.08, P = 0.106, respectively). In conclusion, clinically significant bleeding and ischemic rates were similar between DAT and TAT, although TAT >1 month was associated with higher bleeding risk.